2019
DOI: 10.3390/genes10080565
|View full text |Cite
|
Sign up to set email alerts
|

PARP Inhibitors in Prostate Cancer–the Preclinical Rationale and Current Clinical Development

Abstract: Prostate cancer is globally the second most commonly diagnosed cancer type in men.Recent studies suggest that mutations in DNA repair genes are associated with aggressive forms ofprostate cancer and castration resistance. Prostate cancer with DNA repair defects may bevulnerable to therapeutic targeting by Poly(ADP‐ribose) polymerase (PARP) inhibitors. PARPenzymes modify target proteins with ADP‐ribose in a process called PARylation and are inparticular involved in single strand break repair. The rationale behi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 106 publications
0
71
0
1
Order By: Relevance
“…As noted above, under Cell Biology, PARP inhibitors can improve mitochondrial function and may preserve muscle mass ( 34 40 ). Thus, PARP inhibitors need to be further evaluated for impact on sarcopenia, especially in malignancies where they are already part of the therapeutic armamentarium such as breast, ovarian, pancreas, and some cases of prostate cancer ( 128 131 ). Interestingly, dietary supplementation of NAD+ and/or its precursors is currently undergoing extensive investigation to promote healthy aging ( 132 , 133 ), although specific information on sarcopenia is not available.…”
Section: Physical Activity Muscle Mass and Functional Status In Oldmentioning
confidence: 99%
“…As noted above, under Cell Biology, PARP inhibitors can improve mitochondrial function and may preserve muscle mass ( 34 40 ). Thus, PARP inhibitors need to be further evaluated for impact on sarcopenia, especially in malignancies where they are already part of the therapeutic armamentarium such as breast, ovarian, pancreas, and some cases of prostate cancer ( 128 131 ). Interestingly, dietary supplementation of NAD+ and/or its precursors is currently undergoing extensive investigation to promote healthy aging ( 132 , 133 ), although specific information on sarcopenia is not available.…”
Section: Physical Activity Muscle Mass and Functional Status In Oldmentioning
confidence: 99%
“…2,4,17,[34][35][36] The potency of trapping PARP enzymes differ significantly between inhibitors, with a trapping efficiency following a downstream fashion: talazoparib, niraparib, olaparib, rucaparib, and veliparib. 37 (►Figs. 2 and 3) The last study published was the PROfound phase 3 openlabel trial, which evaluated PARPi (olaparib) in men with mCRPC who had progressed receiving an androgen-signaling-targeted inhibitor (enzalutamide or abiraterone).…”
Section: Discussion Precision Medicine and Genomic Markersmentioning
confidence: 99%
“…36,39 Thus, these findings encouraged the FDA to grant priority review of these two drugs. 36,37,39 The recently published TOPARP-B phase 2 trial (2019) aimed to evaluate the association between DDR gene alterations in mCRPC and response to olaparib 300 mg or 400 mg. Results showed that olaparib has antitumor activity against mCRPC with DDR alterations; the composite response was 54.3% in the 400 mg arm versus 39.1% in the 300 mg arm, suggesting that the ideal dose should be 400 mg, twice a day (at a expense of higher toxicity).…”
Section: Discussion Precision Medicine and Genomic Markersmentioning
confidence: 99%
See 2 more Smart Citations